Indigenous cultural property and international law restitution, rights and wrongs - Esterling, Shea Elizabeth 1978- (Abingdon, Oxon Routledge, 2024)
Examining the restitution of cultural property to Indigenous Peoples in human rights law, this book offers a detailed analysis of the opportunities and constraints of international law as a tool of resistance and social transformation for marginalized groups. In accordance with an increasing insistence on respect for diverse cultures, and through their own international mobilization, Indigenous Peoples have participated in the construction of a distinct human rights framework. Significant academic inquiry has focused on the substantive gains made by Indigenous Peoples in this context; along with its impact on a body of law that had previously denied Indigenous Peoples a basis for claims to their own cultural materials and practices. Accordingly, this book acknowledges that Indigenous Peoples, as non-state actors, have generated greater substantive and procedural legitimacy in human rights law making. Offering normative insights into the participation of non-state actors in international law making, it also, however, demonstrates that, despite their significant role in constructing the legal framework of human rights in the 21st century, the participation of Indigenous Peoples continues to be structurally limited. With its interdisciplinary approach to the field, this book will appeal to scholars and students in the fields of law, politics, anthropology and indigenous studies"--
A textual analysis : Article 11 of the United Nations Declaration on the Rights of Indigenous People--A purposive analysis : Article 11 of the United Nations Declaration on the Rights of Indigenous Peoples--A contextual analysis : Article 11 of the United Nations Declaration on the Rights of Indigenous Peoples--Discursive limits : Article 11 of the United Nations Declaration on the Rights of Indigenous Peoples and Human Rights Law--Some conclusions.
Based on author's thesis (doctoral - Aberystwyth University, 2015) issued under title: Cultural property at the crossroads : an examination of the issue of the restitution of cultural property to indigenous peoples in Article 11 of the United Nations Declaration on the Rights of Indigenous Peoples
Includes bibliographical references and index.
Keywords: United Nations. -- General Assembly; Reparations for historical injustices; Cultural property -- Protection (International law); Indigenous peoples -- Legal status, laws, etc..